Limit of Sums

Calculus Level 3

lim n k = 1 n k 2 ( n + 1 k ) k = 1 n k 3 = a b \large \lim _{ n\rightarrow \infty }{ \frac { \sum _{ k=1 }^{ n }{ { k }^{ 2 }( n+1-k) } }{ \sum _{ k=1 }^{ n }{ { k }^{ 3 } } } } =\frac { a }{ b }

If the equation above holds true for coprime positive integers a a and b b , find 2 a + 3 b 2a+3b .


This Question is Part of My Mathematics Set


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Joseph Newton
Dec 26, 2017

lim n k = 1 n k 2 ( n + 1 k ) k = 1 n k 3 = lim n k = 1 n k 2 ( n + 1 ) k = 1 n k 3 k = 1 n k 3 = lim n ( n + 1 ) k = 1 n k 2 k = 1 n k 3 1 \lim_{n\rightarrow\infty}{\frac{\sum\limits_{k=1}^n{k^2(n+1-k)}}{\sum\limits_{k=1}^n{k^3}}}\\ =\lim_{n\rightarrow\infty}{\frac{\sum\limits_{k=1}^n{k^2(n+1)-\sum\limits_{k=1}^n{k^3}}}{\sum\limits_{k=1}^n{k^3}}}\\ =\lim_{n\rightarrow\infty}{\frac{(n+1)\sum\limits_{k=1}^n{k^2}}{\sum\limits_{k=1}^n{k^3}}-1} Now we can use the formulas for the sum of the first n squares and cubes: k = 1 n k 2 = n ( n + 1 ) ( 2 n + 1 ) 6 k = 1 n k 3 = n 2 ( n + 1 ) 2 4 \begin{aligned}\sum\limits_{k=1}^n{k^2}&=\frac{n(n+1)(2n+1)}{6}&&&\sum\limits_{k=1}^n{k^3}&=\frac{n^2(n+1)^2}{4}\end{aligned} lim n ( n + 1 ) k = 1 n k 2 k = 1 n k 3 1 = lim n ( n + 1 ) n ( n + 1 ) ( 2 n + 1 ) 6 n 2 ( n + 1 ) 2 4 1 = lim n 4 n ( 2 n + 1 ) 6 n 2 1 = lim n 4 n 2 + 2 n 3 n 2 1 = lim n 4 + 2 n 3 1 = 4 3 1 = 1 3 \begin{aligned}\lim_{n\rightarrow\infty}{\frac{(n+1)\sum\limits_{k=1}^n{k^2}}{\sum\limits_{k=1}^n{k^3}}-1}&=\lim_{n\rightarrow\infty}{\frac{(n+1)\frac{n(n+1)(2n+1)}{6}}{\frac{n^2(n+1)^2}{4}}-1}\\ &=\lim_{n\rightarrow\infty}{\frac{4n(2n+1)}{6n^2}-1}\\ &=\lim_{n\rightarrow\infty}{\frac{4n^2+2n}{3n^2}-1}\\ &=\lim_{n\rightarrow\infty}{\frac{4+\frac{2}{n}}{3}-1}\\ &=\frac{4}{3}-1\\ &=\frac{1}{3}\end{aligned} So the final answer is 2 ( 1 ) + 3 ( 3 ) = 11 2(1)+3(3)=\boxed{11}

L = lim n k = 1 n k 2 ( n + 1 k ) k = 1 n k 3 = lim n ( n + 1 ) k = 1 n k 2 k = 1 n k 3 k = 1 n k 3 = lim n ( n + 1 ) × n ( n + 1 ) ( 2 n + 1 ) 6 n 2 ( n + 1 ) 2 4 1 = lim n 4 ( 2 n + 1 ) 6 n 1 = lim n 4 n + 2 3 n 1 Divide up and down by n = lim n 4 + 2 n 3 1 = 4 3 1 = 1 3 \begin{aligned} L & = \lim_{n \to \infty} \frac {\sum_{k=1}^n k^2(n+1-k)}{\sum_{k=1}^n k^3} \\ & = \lim_{n \to \infty} \frac {(n+1)\sum_{k=1}^n k^2-\sum_{k=1}^n k^3}{\sum_{k=1}^n k^3} \\ & = \lim_{n \to \infty} \frac {(n+1)\times \frac {n(n+1)(2n+1)}6}{\frac {n^2(n+1)^2}4} - 1 \\ & = \lim_{n \to \infty} \frac {4(2n+1)}{6n} - 1 \\ & = \lim_{n \to \infty} {\color{#3D99F6}\frac {4n+2}{3n}} - 1 & \small \color{#3D99F6} \text{Divide up and down by }n \\ & = \lim_{n \to \infty} \frac {4+\frac 2n}3 - 1 \\ & = \frac 43 - 1 = \frac 13 \end{aligned}

Therefore, 2 a + 3 b = 2 ( 1 ) + 3 ( 3 ) = 11 2a+3b = 2(1)+3(3) = \boxed{11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...